Urban regeneration and the transformation of the urban waterfront: a case study of Liverpool waterfront regeneration - Hussein, Mohamed M. Fageir (2015)
The transformation of urban waterfronts is one of the key urban design and planning stories of the late twentieth century. The decline of the waterfront in post-industrial cities meant the deterioration of both a physical and social nature of significant portions of urban fabric. Cities have reacted to this state of affairs with substantial regeneration programs, approaching the decline of waterfront as an opportunity rather than a problem. However, since the success of early regeneration programs in North America, changing urban waterfronts on a global scale has led to a manifestation of globalisation, becoming a synonym of uniformity and monotony of cities. The urban waterfront also has become a battleground for a number of intersecting forces and different interests and desires. This research aims to study the phenomenon of urban waterfront regeneration, specifically analysing how it has operated within the UK context since the late 20th century until the present. It focuses on investigating the process of transformation of the urban waterfront in the city of Liverpool. Liverpool has suffered from a serious urban decline following the degeneration of its seven miles of docks due to a number of internal and external factors. However, since the 1980s, the image of an abandoned waterfront has started to change with massive waterfront regeneration schemes that aim to improve the physical, environmental, social and economic conditions of the area. This research argues that by understanding the process and the context of this regeneration, several lessons can be learned and models of good practice can be identified. The research is based on a series of lengthy interviews with key stakeholders closely linked with the development in the city, a review of documents related to the regeneration of Liverpool waterfront, including urban design policies and guidance, a substantial review of relevant news articles that were written throughout the periods of the recent transformation of the city, and numerous site visits to reflect upon the development carried out recently. The research also identifies and discusses a number of key urban issues such as image and identity, cultural built heritage, place marketing and branding, urban governance. The research identifies three distinctive eras of waterfront regeneration and several key regeneration schemes. Each of these eras reflects the many factors that shaped the urban landscape. The research argues that there are no specific models that can create successful waterfront regeneration, yet, what is important is ensuring the complexity and the inclusiveness of the process of the regeneration. An inclusive and a complex process will result in attaining urban competitiveness besides securing distinctive, genuine and imaginative urban identity. The research also highlighted the central role of urban design as a mediator between the numerous processes and different forces that shape the urban landscape.